2011
DOI: 10.1080/17455030.2011.613954
|View full text |Cite
|
Sign up to set email alerts
|

Far-field sub-wavelength imaging and focusing using a wire medium based resonant metalens

Abstract: This is the second article in a series of two dealing with the concept of "resonant metalens" we introduced recently [Phys. Rev. Lett. 104, 203901 (2010)]. It is a new type of lens capable of coding in time and radiating efficiently in the far field region sub-diffraction information of an object. A proof of concept of such a lens is performed in the microwave range, using a medium made out of a square lattice of parallel conducting wires with finite length. We investigate a sub-wavelength focusing scheme with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…In the following, we explain, based on the soda can metamaterial example, how and under which conditions they can indeed be used. The reader has to keep in mind that the soda can medium is a very good airborne acoustic example for this study which has been published in [25], but similar results have been obtained in underwater acoustics in the ultrasonic range with a bubble as a unit cell [44], with Lamb waves in a thin plate [45], in electromagnetics in the microwave regime [27,46], and in the optical range [47,48], making this approach very robust and general.…”
Section: Subwavelength Focusing In the Context Of Metamaterialsmentioning
confidence: 80%
“…In the following, we explain, based on the soda can metamaterial example, how and under which conditions they can indeed be used. The reader has to keep in mind that the soda can medium is a very good airborne acoustic example for this study which has been published in [25], but similar results have been obtained in underwater acoustics in the ultrasonic range with a bubble as a unit cell [44], with Lamb waves in a thin plate [45], in electromagnetics in the microwave regime [27,46], and in the optical range [47,48], making this approach very robust and general.…”
Section: Subwavelength Focusing In the Context Of Metamaterialsmentioning
confidence: 80%
“…Alternative approaches have been proposed for sub-diffraction-limited imaging utilizing inversion procedures with far-field detection, including time reversal, optical diffraction tomography (ODT) and compressed sensing [65][66][67][68][69][70] . The time-reversal technique was first introduced as an inversion method for electromagnetic waves and was experimentally demonstrated by subwavelength focusing and imaging of microwaves 65,66,[71][72][73][74][75] . Evanescent waves that carry small details are converted into propagating waves by placing a subwavelength object made of monopoles in the near field of a cluster of strongly coupled resonators, referred to as a 'resonant metalens' (Fig.…”
Section: Extraordinary Imaging Properties Of the Hyperbolic Metalensmentioning
confidence: 99%
“…Based on the reciprocity of the system, not only propagating waves but also evanescent waves can be recovered at the monopole location. An image with a sub-diffraction-limited resolution of l/80 has been reconstructed by cross-correlation between the received signals and the filters 66,72 . An extension to 2D imaging is possible by using a total internal reflection configuration 72 .…”
Section: Extraordinary Imaging Properties Of the Hyperbolic Metalensmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulations based on this idea 92 have shown that wavefront shaping can be used to focus monochromatic light to subwavelength spots in an array of split rings. In this monochromatic approach, coupling between resonators gives rise to spatial sidelobes that are suppressed when using polychromatic signals 93,94 .…”
Section: The Medium As the Lensmentioning
confidence: 99%